Lived experiences related to the identity of black African adolescents - Arndt, Natasha (University of the Free State, 2014)
In this study the lived experiences related to the identity of black African adolescents in the Motheo district of central South Africa were explored. South Africa continues to experience political, economic and social changes. Given the new democracy and the opportunities available to all South African youths, the lived experiences of black African adolescents have been noticeably transformed. However, a paucity of qualitative research is found regarding the lived experiences related to the identity of black African adolescents currently in South Africa. The research is approached from an interpretivist paradigm and Bronfenbrenner’s ecological systems theory was taken as the theoretical framework for the study. Existing literature on adolescence and identity was utilised as sensitising concepts for the study. The aim of this study was to give the participants a voice and allow them an opportunity to speak openly about their lived experiences related to their identity. This qualitative research study used focus group discussions as well as individual in-depth interviews to explore participants’ lived experiences. Fifty-nine participants selected from four schools in the Motheo district participated in the study. The data were analysed using Interpretative Phenomenological Analysis, reconstructing participants’ stories into main and subthemes. Four main themes were identified. The first highlighted the participants’ experience and understanding of who they are, the second pertained to the participants’ experience of being themselves in relation to others (family and peers), a third main theme involved participants’ experience of being themselves in their direct environment (school, media, communities and neighbourhood), and, finally, the fourth main theme detailed participants’ experience of being themselves within their ideological structures. The results of this study were confirmed by numerous existing theories and the findings of previous studies. The clinical significance of the study included numerous recommendations for future qualitative research studies so as to add nuanced information to this field.

In hierdie studie is die geleefde ervaringe (lived experiences) rakende die identiteit van swart Afrikane adolessente in die Motheo distrik van sentraal Suid-Afrika ondersoek. Suid-Afrika ondervind steeds politieke, ekonomiese en sosiale veranderinge. Gegewe die nuwe demokrasie en die geleenthede wat beskikbaar is aan alle Suid-Afrikaanse jeugdiges, het die beleefde ervaringe van swart Afrikane adolessente merkbaar verander. Daar is egter gevind dat daar tans beperkte kwalitatiewe navorsing in verband met die geleefde ervaringe rakende die identiteit van swart Afrikane adolessente in Suid-Afrika bestaan. Hierdie navorsing is vanuit ŉ interpretatiewe paradigma benader en Bronfenbrenner se ekologiese sisteemteorie is as teoretiese raamwerk vir hierdie studie aangewend. Bestaande literatuur oor adolessensie en identiteit is gebruik as die bewusmakings-konsepte (sensitising concepts) vir die studie. Die doel van hierdie studie was om die deelnemers 'n stem te gee en hulle 'n geleentheid te bied om openlik te praat oor hul ondervindinge rakende hul identiteit. Hierdie kwalitatiewe navorsing het fokusgroep-besprekings sowel as individuele indiepte onderhoude gebruik om deelnemers se geleefde ervaringe te verken. Nege en vyftig deelnemers vanuit vier skole in die Motheo distrik het aan die studie deelgeneem. Die data is ontleed met behulp van Interpretatiewe Fenomenologiese Analise, waarna deelnemers se stories in hoof- en subtemas gerekonstrueer is. Vier hoof- temas is geïdentifiseer. Die eerste beklemtoon die deelnemers se ervaring en begrip van wie hulle is, die tweede het betrekking op die deelnemers se ervaring van hulself in verhouding tot ander (familie en vriende), 'n derde hooftema handel oor deelnemers se ervaring van hulself in hul direkte omgewing (skool, media, gemeenskappe en buurte), en laastens, die vierde hooftema beklemtoon die deelnemers se ervaring van hulself in hul ideologiese strukture. Bestaande teorieë en bevindinge van vorige studies bevestig die resultate van hierdie studie. Die kliniese belang van die studie sluit verskeie aanbevelings vir verdere kwalitatiewe navorsing studies in, om sodoende genuanseerde inligting tot hierdie veld te bevorder.
Thesis (Ph.D. (Psychology))--University of the Free State, 2014
Keywords: Black African adolescents; Lived experiences; Motheo district; Identity; Interpretative phenomenological analysis; Phenomenological psychology; Personality and culture; Teenagers, Black; Identity (Psychology) in adolescence